Suppression of ZBP1-mediated NLRP3 inflammasome by the tegument protein VP22 facilitates pseudorabies virus infection - Zicheng Ma; Depeng Liu; Wandi Cao; Lei Guo; Kesen Liu; Juan Bai; Xingyi Li; Ping Jiang; Xing Liu (mBio)
ABSTRACT The interaction between Z-DNA binding protein 1 (ZBP1) and the NLR family pyrin domain-containing 3 (NLRP3) inflammasome has been uncovered in several viral infections. However, the role of this molecular pathway during infection with the alpha-herpesvirus pseudorabies virus (PRV) remains largely elusive. Here, we report that during PRV infection, ZBP1-mediated NLRP3 inflammasome activation is inhibited by the viral tegument protein VP22, thereby facilitating viral infection. Through a combination of RNA sequencing and genetic studies, we demonstrate that PRV VP22 functions as a virus-encoded virulence factor by evading the inhibitory effects of ZBP1 on virus infection. Importantly, the replication and pathogenicity of a recombinant PRV lacking VP22 are significantly increased in ZBP1-deficient cells and mice. Mechanistically, PRV VP22 interacts with ZBP1, impeding the recruitment of receptor-interacting protein kinase 3 and Caspase-8, thereby inhibiting NLRP3 activation. Furthermore, we show that the N-terminal 1–50 amino acid domain of VP22 dominantly destabilizes ZBP1-mediated function. Taken together, these findings identify a functional link between PRV infection and ZBP1-mediated NLRP3 inflammatory response, providing novel insights into the pathogenesis of PRV and other herpesviruses.IMPORTANCEZ-DNA binding protein 1 (ZBP1) functions as a pivotal innate immune sensor that regulates inflammatory cell death during viral infections. However, its role in pseudorabies virus (PRV) infection remains unknown. Here, we demonstrate that ZBP1 serves as a restrictive factor by triggering the activation of the NLR family pyrin domain-containing 3 inflammasome, a process counteracted by PRV-encoded protein VP22. Furthermore, VP22 interferes with the interaction between ZBP1 and receptor-interacting protein kinase 3/Caspase-8, particularly through its N-terminal 1–50 amino acids. Importantly, deficiency in ZBP1 enhances the replication and virulence of recombinant viruses lacking VP22 or its N-terminal 1–50 amino acids. These findings reveal how PRV escapes ZBP1-mediated inflammatory responses during infection, potentially informing the rational design of therapeutic interventions.